Public Sector Jobs: Working in the Public Sector in Europe and the US - Daniele Checchi; Alessandra Fenizia; Claudio Lucifora (Institute of Labor Economics (IZA), 2021)
This paper reviews recent theoretical and empirical work on public employment management and presents novel stylized facts on public sector jobs. In the first part, we examine the evolution of managerial practices in the public sector and discuss the contractual arrangement of public sector workers and the labor market institutions that are prevalent in this setting. We argue that, for public sector employees, standard incentive schemes have a low power and are generally less effective than in the private sector. In the second part, we use two international surveys (6th European Working Conditions Survey, covering 28 European countries, and 2nd American Working Conditions Survey for the United States) to investigate selection into public sector employment, public-private pay differentials, and differences in working conditions in Europe and the US. While in Europe the public-private earning gap is positive for low-skilled workers and turns negative for skilled individuals, the gap is negative and relatively flat over the skill distribution in the US. We also document a positive public-private earnings differential in healthcare and education services in Europe, and a negative differential, though not statistically significant, in the US. We find that, in the US, two out of three public sector employees are exposed to some performance-related pay scheme, while in Europe is less than one in four. We do not find evidence that the public sector ensures a fairer work environment, as instances of harassment, discrimination, and obnoxious behavior are widespread.
Keywords: J45; J31; H50; 330; public sector; managerial practices; public-private pay differentials; working conditions